PENINGKATAN HASIL BELAJAR IPAS KELAS V SDN PANDANWANGI 3 MELALUI PENDEKATAN CULTURALLY RESPONSIVE TEACHING - Wahyuanna Azzunny, Nabila; Thohir, M. Anas; Amzah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The application of the Culturally Responsive Teaching (CRT) approach in this research aims to improve students' learning outcomes. This research is a type of Classroom Action Research (CAR), which is carried out in class V IPAS learning at SDN Pandanwangi 3 within a span of 2 learning cycles. Data collection in this research was through observation, written tests, documentation, and students' reflections. Meanwhile, to obtain more comprehensive and valid data, the data in this research were analyzed using mixed methods, which combine quantitative and qualitative approaches. Starting at the pre-cluster stage, researchers found that only 37.93% of students had reached mastery, while 62.07% of students were not yet complete. Afterwards, by applying the CRT approach, in cycle I the results showed that 51.72% of students had reached mastery, 48.28% of students were not yet complete. Whereas in cycle II, there was a significant increase in results, namely there were 82.76% of students who had completed, and only 17.24% of students who had not completed. Through these results, it can be seen that there is an increase in the learning outcomes of students in the realm of knowledge, it can be seen that in cycle I 51.72% of students are complete, this result has increased in cycle II, namely 82.76% of students have completed. The findings of this research reveal that the application of the CRT approach can significantly improve students' learning outcomes.